Neuron-specific SALM5 limits inflammation in the CNS via its interaction with HVEM - Zhu, Yuwen (Sci Adv, 2016)
The central nervous system (CNS) is an immune-privileged organ with the capacity to prevent excessive inflammation. Aside from the blood-brain barrier, active immunosuppressive mechanisms remain largely unknown. We report that a neuron-specific molecule, synaptic adhesion-like molecule 5 (SALM5), is a crucial contributor to CNS immune privilege. We found that SALM5 suppressed lipopolysaccharide-induced inflammatory responses in the CNS and that a SALM-specific monoclonal antibody promoted inflammation in the CNS, and thereby aggravated clinical symptoms of mouse experimental autoimmune encephalomyelitis. In addition, we identified herpes virus entry mediator as a functional receptor that mediates SALM5’s suppressive function. Our findings reveal a molecular link between the neuronal system and the immune system, and provide potential therapeutic targets for the control of CNS diseases.